KETERAMPILAN MANAJERIAL KEPALA SEKOLAH - MGS. Ferdi (UNIVERSITAS BENGKULU, 2015)
The general purpose of this study was to determine the skills of junior High School number 7 Lubuklinggau. While the specific purpose of this research are: (1) to describe the conceptual skills of Principal. (2) to describe human relations skills of Principal. (3) to describe the technical skills of Principal. This research used descriptive qualitative method is based on the formulation of research that requires researchers to explore in order to understand and explain the problems examined through an intensive relationship with the source data. In General researcherscan deduce that the Principal of the junior high school number 7 Lubuklinggau.Keywod: managerial skills, principal